Hubungan antara Pemakaian Repellent Anti Nyamuk dan Kejadian Penyakit Demam Berdarah Dengue pada Anak di Kota Surakarta - Sofia, Fika Khulma; Probandari, Ari Natalia; Hikmayani, Nur Hafidha (Jurnal Kedokteran Indonesia, 2012)
Background: Dengue haemorrhagicfever (DHF) is a common mosquito-transmitted infectious disease in tropical and subââ-tropical areas. In Indonesia, the incidence significantly increased from 58 cases in 1968 to 15,912 cases in 2009. Case fatality ratereached over 1% in most provinces. Repellent refers totopical antimosquito agent which can be used to prevent DHF. Repellent contains active substances that prevent mosquito bites such as DEET (N,Nâdietilâmâtoluamid) and permethrine. This study aimed to examine the relationship between use of anti-mosquito repellent and risk of DHF among children in Surakarta. Method: This was an observational study using matched case-control design. It was carried out atfive public health centers in Surakarta with high prevalence of DHF in children during 2010-2012period. Forty cases were selected using cluster sampling method and were matched for age and residence with 40 DHF-free controls. Questionnaires were used to identify use of repellent. Other data collected included frequency, habit,timing and duration of repellent use. Data were analyzed by McNemarâs Ï2test and conditional logistic regressionsusing OpenEpi 2.0 and Stata SE 12.0. Results: McNemarâs Ï2 test showed a significant relationship between use of antimosquito repellent and DHF (p<0.001). Children usingantimosquito repellent had 0.04 times the risk for DHF than those not using repellent (OR=0.04, 95%CI= 0.01 to 0.23). Regression analysis showed that frequency and timing of repellent use were significantly associated with DHF. Compared to children who did not use repellent, children using repellent often (5-7 times a week) had0.12 times the risk for DHF (OR=0.12,95%CI=0.02 to 0.60; p=0.011).Children using repellent after 8 pm had0.22 times the risk for DHF (OR=0.22, 95% CI=0.01 to 0.70; p=0.022). Habit and duration of repellent use showed no statistically significant association with DHF (p>0.05). Conclusion: Use of repellentsignificantly reduces the risk for DHF among children in Surakarta. Frequent and nocturnal useofrepellentare protective factors for DHF.Keywords: Dengue haemorrhagic fever, antimosquito repellent, children